Expression and cellular localization of the classical progesterone receptor in healthy and amyotrophic lateral sclerosis affected spinal cord - Gargiulo Monachelli, Gisella Mariana (2014)
Background and purpose Previous studies have suggested that elevated progesterone levels are associated with a slower disease course in amyotrophic lateral sclerosis (ALS). Given that the effects of progesterone are mediated in part by the classical progesterone receptor (PR), the expression and cellular localization of the A and B isoforms (PR-A and PR-B, respectively) of the PR in control (neuropathologically normal) and ALS-affected spinal cord (SC) were examined. Methods Semi-quantitative RT-PCR, immunohistochemistry and immunofluorescence analyses of the cervical and lumbar SC of post-mortem ALS patients (n = 19) and control subjects (n = 10) were performed. Primers and antibodies used allowed the detection of both PR-A and PR-B isoforms together (PR-A+B) or PR-B isoform alone. Results Lumbar PR-A+B and cervical PR-B mRNA expression were significantly higher in ALS than controls. In both ALS and controls, PR-A+B immunoreactivity (IR) was occasionally detected in motor neurons. In contrast, PR-A+B IR was prominent in axonal processes and vessels. This was more evident in nerve roots and large arteries in ALS compared with controls. Colocalization of PR-A+B with markers of neurons, axonal processes and vascular endothelium was also observed. Conclusions Evidence that both PR-A and PR-B isoforms are expressed in the human SC is provided, with some regional variation in isoform expression between ALS and controls. The IR was more prominent in nerve roots and large arteries in ALS, suggesting a potential role in the degenerative process.